Caracterización morfo-estructural y faneroptica del cerdo negro negro en la Provincia de Esmeraldas. - Fajardo Almeida, Fabian Eduardo (2016)
The research project entitled. Objective: To evaluate the control Ceramidia banana (Musa spp), by applying four chitin inhibitors and biological products plantation area Quinsaloma province of Los Rios. The same which consisted of identifying the pest to evaluate cultural practices were carried out on the plantation. Variables that contributed the development of research, such as efficiency of biological and chemical insecticides vs a total absolute control, percentage of leaf damage treatments, leaves with the presence of Ceramidia were recorded. The cost of the application of the treatments was also evaluated. Data analysis consisted of applying a design randomized complete block (RCBD) with the blocking criterion (Application of insecticides and the distance between treatments to avoid overlapping). After obtaining the results and statistical tests signifance proceeded to perform an orthogonal analysis, the same as recorded contracts between the products used to determine the most efficient control Ceramadia. The application of the products demonstrated that T5 (Gusanol) obtained improvements characteristics regarding efficiency control Ceramidia. However in the variables analyzed T4 (Match) won the best values for the number of dead larvae after application. Similarly for cost of implementing it obtained the T4 (Match) with $ 82.80 in controlling Ceramidia. Keywords: Ceramidia, chitin inhibitors, larvae.